THE EFFECT OF ADDITION DIFFERENT DOSAGE BOSTER FERMENTATION TOWARDS GROWTH PERFORMANCE AND SURVIVAL RATE OF SRIKANDI TILAPIA (Oreochromis niloticus) ON BRACKISH WATER - Selviana Niki Fitria; Niken Ayu Pamukas; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research aims was to determine the optimal dosage of different boster fermentation in improving the growth and survival rate of the tilapiasrikandi fish (Oreochromis niloticus) which wasreared in brackish water by using a boster system. This research was conducted on April 2018 until June 2018 held at UPT Fish Hatchery and Experimental Pond Faculty of Fisheries and Marine University of Riau (FPK UNRI). The design of this research is an experimental model using Completely Randomize Design Factorial pattern (RAL) of 1 factor, 5 treatment levels and 3 replications. Treatment in this research was respectively; 0 ml/Lrearing tank (P0), 0.075 ml/Lrearing tank (P1), 0.45 ml/Lrearing tank (P2), 0.825 ml/lrearing tank (P3) and 1.2 ml/Lrearing tank (P4). The results showed that the different doses of boster fermentation influenced the growth performance and survival rate of tilapia srikandi by using boster system in brackish water rearing media. The best dosage was found at 0.45 ml/Lrearing tank of boster fermentationby giving the absolute weight growth was 30.33 g, absolute length was 6.53 cm, daily growth ratewas  4.64%, survival rate was 88.33%, feed efficiency was 122,97% and feed conversion ratio was 0.82. Water quality range at all treatments were: The temperature ranges was from 26 to 29 oC, pH ranges was from 6.5 to 8, and DO ranges was from 4.4 to 6.4 mg/L, CO2 ranges was from 2.00 to 3.33 and ammonia was around 0,0007-0,054 mg/L.                                                                                      Keyword :Fermentation, boster, srikandi tilapia, brackish water